2018
DOI: 10.1371/journal.pone.0195097
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Mediterranean fruit fly [Ceratitis capitata (Wiedemann)] spatio-temporal distribution in relation to sex and female mating status for precision IPM

Abstract: The Mediterranean fruit fly (medfly), Ceratitis capitata (Wiedemann), is a key pest of fruit crops in many tropical, subtropical and mild temperate areas worldwide. The economic importance of this fruit fly is increasing due to its invasion of new geographical areas. Efficient control and eradication efforts require adequate information regarding C. capitata adults in relation to environmental and physiological cues. This would allow effective characterisation of the population spatio-temporal dynamic of the C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 48 publications
0
24
0
1
Order By: Relevance
“…Theoretical models predicting outcomes of mating interactions relative to emergence time (Morbey & Ydenberg, ) have met diverse empirical observations: female mating probability may be higher in early, middle, or late phases of emergence cycles. In many instances, low female mating probability on a given day coincides with rarity of males (Calabrese & Fagan, ; Franco et al., ; Calabrese et al., ; Rhainds, ; Fauvergue, ; Faust & Forrest, ; Sciarretta et al., ). These studies support widely held views of female‐biased sex ratios and/or acute shortage of males (‘male vacuum’) as triggers of FMF (Wing, ; Mendel et al., ; Fritzsche et al., ).…”
Section: Effects Of Emergence Time On Mating Failurementioning
confidence: 99%
See 1 more Smart Citation
“…Theoretical models predicting outcomes of mating interactions relative to emergence time (Morbey & Ydenberg, ) have met diverse empirical observations: female mating probability may be higher in early, middle, or late phases of emergence cycles. In many instances, low female mating probability on a given day coincides with rarity of males (Calabrese & Fagan, ; Franco et al., ; Calabrese et al., ; Rhainds, ; Fauvergue, ; Faust & Forrest, ; Sciarretta et al., ). These studies support widely held views of female‐biased sex ratios and/or acute shortage of males (‘male vacuum’) as triggers of FMF (Wing, ; Mendel et al., ; Fritzsche et al., ).…”
Section: Effects Of Emergence Time On Mating Failurementioning
confidence: 99%
“…Natural mating disruption (high rates of FMF on crowded host plants) can arise due to: (1) males being unable to discriminate receptive females from conspecific males or non receptive females (Richerson et al, 1976;Takeuchi, 2017;Sales et al, 2018), (2) passive olfactory signals of post reproductive conspecifics interfering with mate location (Gwynne & Lorch, 2013;Rhainds, 2018), or (3) adsorption of pheromone onto the foliage of host plants (Noldus et al, 1991). Testing these hypotheses requires small-scale mapping of female mating probability among georeferenced plants (van Wijk et al, 2017;Muniz et al, 2018;Sciarretta et al, 2018).…”
Section: Signal Interference and Natural Mating Disruptionmentioning
confidence: 99%
“…This approach increased the possibility to perform unnecessary treatments, especially when repeated low catches were found in most traps. Due to this extra cautious approach, only 23% of the DSS spraying recommendations reported a capture aggregation, even though it has been reported that medfly in this area and elsewhere tends to significantly aggregate, especially under low population densities [26,27]. Even with these limitations, the application of the DSS algorithm allowed us to differentiate insecticide applications for each cultivar, resulting in precision targeting treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Geospatial tools provide a greater understanding of the pest dynamics and its spatial relationships with a surrounding environment (Ellsbury et al, ; Fleischer, Blom, & Weisz, ; Liebhold, Rossi, & Kemp, ). More recently, the modelling of the spatial behaviour of pest species of Tephritidae such as A. ludens, Bactrocera oleae Rossi and C. capitata incorporated GIS and geostatistics applications (Castrignanò et al, ; Papadopoulos, Plant, & Carey, ; Sciarretta et al, ; Vanoye‐Eligio, Barrientos‐Lozano, Pérez‐Castañeda, Gaona‐García, & Lara‐Villalon, ). Moreover, the analysis of spatio‐temporal patterns of adult captures has become a technical base for conducting specific strategies against the Medfly, C. capitata , over the last years (Cohen et al, ; Enkerlin et al, ; Midgarden, Lira, & Silver, ).…”
Section: Introductionmentioning
confidence: 99%